To solve the first equation, we will simplify both sides:
2(u + 2) - u = 3(u - 1) + 9
2u + 4 - u = 3u - 3 + 9
u + 4 = 3u + 6
Next, we will move all the variables to one side of the equation and the constants to the other side:
u - 3u = 6 - 4
-2u = 2
Now, we will isolate u by dividing both sides by -2:
u = 2/-2
u = -1
Therefore, the first equation has one solution: u = -1.
For the second equation:
4(w + 1) - w = 3(w - 1) + 7
4w + 4 - w = 3w - 3 + 7
3w + 4 = 3w + 4
In this case, we notice that the variables cancel out, and we are left with a true statement: 4 = 4. This means that the equation is always true, regardless of the value of w.
Therefore, the second equation has infinite solutions.
For each equation find if it has infinite solutions no solutions or one solution. If it has one solution give the solution.
2(u+2)-u=3(u-1)+9
4(w+1)-w=3(w-1)+7
1 answer